Validity test digital booklet of human digestive system for students in class XI senior high school - Lailatil Arifah; Ardi Ardi; Syamsurizal Syamsurizal; Helsa Rahmatika; Suci Fajrina; Ani Murianti; Fifi Mardayanti (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
Learning media is everything that is used to distribute information in learning. The use of appropriate and varied media can overcome the passive nature of students in the teaching and learning process. The results of the analysis of observational questionnaires on students and teachers, it is known that the media that tend to be used are textbooks and modules. Therefore, teachers and students still want other learning media that are able to attract interest in reading and can easily be used anytime and anywhere by students. Based on this, a digital booklet on the material of the human digestive system was developed as a valid learning medium for class XI SMA/MA students. This research was conducted at the Department of Biology, FMIPA UNP and SMAN 1 Rao, using a 4D development model (define, design, develop and disseminate) which is abbreviated at the develop (3D) stage. The data obtained were analyzed by descriptive statistics. The average value of validation is 90.95% with a very valid category. This criterion was obtained from four aspects tested, namely aspects of the feasibility of content, language, presentation and graphics. Digital booklets with very valid criteria are appropriate for use in the student learning process.Abstrak Media pembelajaran merupakan segala sesuatu yang digunakan untuk menyalurkan informasi dalam pembelajaran. Penggunaan media yang tepat dan bervariasi dapat mengatasi sifat pasif perserta didik dalam proses belajar mengajar. Hasil analisis angket observasi terhadap peserta didik dan guru, diketahui media yang cenderung digunakan adalah buku teks dan modul. Oleh karena itu guru dan peserta didik masih menginginkan media pembelajaran lain yang mampu menarik minat baca dan dengan mudah dapat digunakan kapan dan dimana saja oleh peserta didik. Berdasarkan hal tersebut dikembangkanlah booklet digital pada materi sistem pencernaan manusia sebagai media pembelajaran yang dilengkapi dengan gambar dan video yang interaktif untuk peserta didik kelas XI SMA/MA yang valid. Penelitian ini dilakukan di Departemen Biologi FMIPA UNP dan SMAN 1 Rao, dengan menggunakan model pengembangan 4D (define, design, develop dan disseminate) yang disingkat pada tahap develop (3D). Data yang diperoleh dianalisis secara statistik deskriptif.  Nilai rata-rata validasi 90,95% dengan kategori sangat valid. Kriteria ini diperoleh dari empat aspek yang diuji yaitu aspek kelayakan isi, kebahasaan, penyajian dan kegrafikaan. Booklet digital dengan kriteria sangat valid layak digunakan dalam proses belajar oleh siswa.